The 400-m front crawl test: Energetic and 3D kinematical analyses - Correia, R. de Assis; Feitosa, W. Gomes; Figueiredo, P.; Papoti, M.; Souza Castro, F. A. (International Journal of Sports Medicine, 2020)
The aim of the study was to verify the relative contributions of energetic and kinematic parameters to the performance in 400-m front crawl test. Fourteen middle-distance swimmers participated in the study. Oxygen consumption was measured directly and blood samples were collected to assay lactate concentration. Both oxygen consumption and lactate concentration were used to calculate the: (i) overall energy expenditure, (ii) anaerobic (alactic and lactic) and (iii) aerobic contributions. The mean centre of mass speed and intracycle velocity variation were determined through three-dimensional kinematic analysis. Mean completion time was 315.64±26.91s. Energetic contributions were as follows: 6.1±0.28% from alactic anaerobic metabolism, 5.9±0.63% from anaerobic lactic and 87.8±0.88% from aerobic. Mean intracycle velocity variation was 0.14±0.03. The results indicated that performance of 400-m test relies predominantly on aerobic power. Parameters such as lactate, mean speed, anaerobic lactic and alactic (kW) correlated with performance of 400-m test (p <0.05). Multiple linear regressions indicated that mean centre of mass speed and anaerobic alactic (kW) determined the 400-m test performance (R2=0.92). Even though the T400 is characterized by aerobic metabolism, the anaerobic alactic component cannot be negligible at this competition level.